Correlation between HPV infection and human beta-defensin mRNA expression in pterygium and normal conjunctiva epithelial cells - Aliyu, Abubakar Saadatu (2017)
Pterygium is a wing-shaped fibro-vascular proliferative lesion that originates from the bulbar conjunctiva and spreads to the corneal limbus and beyond.They are often seen on the nasal side horizontally in the interpalpebral fissure, but may appear on temporal sides too. It is known to cause irregular astigmatism which can compromise vision, corneal scarring, and restriction of ocular motility or ocular surface inflammation. Human β-defensins (HBDs) and viral oncogene such as human papillomavirus (HPV) may be involved in its etiology and development which are still a matter of contention. The aim of this study is to establish the relationship between HPV infection and human β-defensins mRNA gene expression in pterygium. Thirty pterygium and 30 normal conjunctiva epithelial samples were used in the study. Genomic DNA extracted from pterygium and normal conjunctiva was used to determine HPV-DNA using consensus general primer (GP5+/6+) by real time-PCR assay. Subsequently, HPV specific type 16 and 18 primers were used in HPV infected samples for subtyping. Human β -defensins DEFB1, DEFB4A, and DEFB109 mRNA expression were evaluated using real-time PCR and ΔΔ-Ct method was used to calculate relative quantification of human beta defensins (HBDs) in Pterygium and normal conjunctiva epithelial cells. The relationship between HPV infection and human beta- defensins was analysed by Spearman's non parametric correlations for each bivariate pair. HPV viral DNA was detected in 29 of 30 Pterygium and 10 of 30 normal conjunctiva samples respectively, HPV 18 was the most common viral type identified. The expression of human β -defnsins DEFB1 and DEFB4A were up-regulated in pterygium when compared with that of normal conjunctiva of the same patient, while no significant difference was observed in DEFB4A expression. However, the expression of DEFB109 was significantly down- regulated in pterygium compared to that of normal conjunctiva. Finally, there was positive correlation in DEFB1 and DEFB4A expression with HPV infection in normal conjunctiva epithelial cells. The current data suggest that HPV and HBDs may play a crucial role in pterygial development thus, may be considered as novel molecular target in understanding pterygium pathogenesis.